Preliminary report on the development of movement analysis for the sport selection of gidran horses - Jónás, Sándor; Drén, Csaba A.; Hecker, Walter (Acta Agraria Kaposváriensis, 2007)
The last horse breed of the once world wide famous horse producing of the historical Hungary that survived almost completely is the gidran. The reservation of this excellent but because of its small number, endangered population is extremely important for our national pride and animal breeding culture. The aim of this research is to develop a process of sport selection for the gidran horse breed. Knowing the fact that among the characteristics that are important in the horse sports, the character, the attitude, the ridability, quality of the basic movements and the ability to jump are highlighted. From these, the basic movement and the ability to jump have the highest inheritance, and above all these can the most objectively be measured. For these it seems reasonable trying to find a selection method that is based on the above mentioned characteristics. It is to keep in mind that because of the low number of gidrans, efficacy of the selection and some other economically important facts, it is important to obtain objective informations as early as possible to help selection. It seems that our method is capable not only to find those individuals that can perform well, but the ones that at same time have a positive influence on the breed too. Those horses that had been tested with this method and have been shown in competitions prove not only the effectiveness of the testing method but the excellence of the gidrans as well.
Keywords: gidran; marker points; movement analysis; free jumping corridor